Navigating supply chain management: Technology adoption in Southeast Nigerian breweries - Ugwu, Kelechi Enyinna; Balogun, Olu (YAYASAN MITRA PERSADA NUSANTARA, 2024)
The study focuses on evaluating the influence of the adoption of technological advancement on supply chain management in Selected Nigerian Brewery Plc, South-East Zone Nigeria. The research employed a survey design and questionnaire as instruments for data collection. The total population of the study comprised 2,100 staff of the organization. Taro Yamane method was used to estimate the sample size which produced a result of 336. A proportionate allocation formula was applied in the distribution of the survey in the following states: River State, Bayelsa, Akwa Ibom, Delta, and Edo State, Nigeria. Out of 336 copies of a questionnaire sent to the participants, only 321 were returned and utilized for the study while the remaining 15 copies were not utilized for this study. The study hypotheses were statistically tested and analyzed using Pearson correlation methods at a 5% significance level. The findings of research hypothesis one indicates that artificial intelligence (AI) adoption positively contributes to supply chain visibility (SCV) when the p-value (.000) is less than a 5 % level of significance (p < 0.05). The researcher recommends that businesses should create a demand forecast based on using historic sales to meet customer demands. Management of the Nigerian Brewery Plc should continue to invest in advanced technologies such as AI and IoT to further enhance supply chain operations. This will help maintain a competitive edge in the market by improving efficiency and reducing costs. This study adds to the body of knowledge by presenting data on the beneficial effects of technology improvements on supply chain management in the Nigerian brewery industry. The study would guide the Nigerian government to implement e-government, and e-health services to citizens.